CHANGES IN THE MORPHOLOGICAL PARAMETERS OF THE SMALL INTESTINE IN SEVERE TRAUMATIC BRAIN INJURIES (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The proven relationship between a critical condition and changes in intestinal morphology in neurosurgical patients is a justification for the need to continue research aimed at developing a strategy for their treatment, including the prevention of secondary damage to the brain and other body systems. The results of the analysis of literature data on changes in the morphological parameters of the small intestine in severe traumatic brain injuries are presented.